2007
DOI: 10.1063/1.2719158
|View full text |Cite
|
Sign up to set email alerts
|

Transition between grain boundary and intragrain scattering transport mechanisms in boron-doped zinc oxide thin films

Abstract: A comprehensive model for the electronic transport in polycrystalline ZnO:B thin films grown by low pressure chemical vapor deposition is presented. The optical mobilities and carrier concentration calculated from reflectance spectra using the Drude model were compared with the data obtained by Hall measurements. By analyzing the results for samples with large variation of grain size and doping level, the respective influences on the transport of potential barriers at grain boundaries and intragrain scattering… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
132
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 238 publications
(141 citation statements)
references
References 19 publications
8
132
1
Order By: Relevance
“…4 The aforementioned is supported by Ellmer and Mientus, 5 Minami et al, 6 Steinhauser et al, 7 and Ruske et al 8 Minami et al 6 have concluded that grain boundary scattering is mainly dominant in AZO films with carrier concentrations in the range 10 19 -10 20 cm À3 while the ionized impurity scattering is dominant in layers with carrier concentrations in the range 10 20 -10 21 cm À3 . Steinhauser et al 7 concluded that the grain boundaries do not limit the conductivity for carrier concentrations exceeding 1 Â 10 20 cm À3 based on the comparison between Hall mobility and optical mobility for boron-doped ZnO. By comparing the Hall mobility and the optical mobility, Ruske et al 8 boundaries do not limit the conductivity only for ZnO:Al films when the electron concentration is above $5 Â 10 20 cm À3 .…”
Section: Introductionmentioning
confidence: 58%
“…4 The aforementioned is supported by Ellmer and Mientus, 5 Minami et al, 6 Steinhauser et al, 7 and Ruske et al 8 Minami et al 6 have concluded that grain boundary scattering is mainly dominant in AZO films with carrier concentrations in the range 10 19 -10 20 cm À3 while the ionized impurity scattering is dominant in layers with carrier concentrations in the range 10 20 -10 21 cm À3 . Steinhauser et al 7 concluded that the grain boundaries do not limit the conductivity for carrier concentrations exceeding 1 Â 10 20 cm À3 based on the comparison between Hall mobility and optical mobility for boron-doped ZnO. By comparing the Hall mobility and the optical mobility, Ruske et al 8 boundaries do not limit the conductivity only for ZnO:Al films when the electron concentration is above $5 Â 10 20 cm À3 .…”
Section: Introductionmentioning
confidence: 58%
“…8 There are several deposition techniques applied to synthesize ZnO, such as sol-gel, 14 spray pyrolisis, 15 magnetron sputtering, [16][17][18] pulsed laser deposition, 19,20 atomic layer deposition, 21,22 and metalorganic chemical vapor deposition (MO-CVD). 23 Gas phase-based techniques, as MO-CVD, have also shown potential to grow high quality aluminumdoped ZnO (ZnO:Al) layers 24,25 at deposition rates as high as $14 nm/s 26 on a large surface area (>10 cm 2 ). 25,26 In the plasma CVD techniques, the overall heat load of the process is lowered, as the substrate temperature is reduced down to the range of 100-200 C. For example, in the past years, we have shown that the expanding thermal plasma (ETP) leads to good quality ZnO:Al layers deposited up to 1 nm/s with a resistivity of 8 Â 10 À4 X cm for 1100 nm film thickness, at a substrate temperature of 200 C, as reported by Volintiru et al 27 One of the drawbacks of the CVD processes, [27][28][29] unlike the sputtering approach, is the development of a gradient in resistivity as function of the film thickness, usually present over a large thickness range.…”
Section: Introductionmentioning
confidence: 99%
“…Instead of q opt , most authors compute the mobility l opt . [29][30][31][32][33][34][35][36][37][38][39][40] The determination of l opt by modeling of optical spectra requires the effective mass m*, whereas the resistivity q opt can be evaluated without knowing m*. As the effective mass is prone to considerable uncertainties, 30,35,36,40 we will focus on the resistivity q opt .…”
Section: Methodsmentioning
confidence: 99%